ASSESSMENT OF THE MAXIMUM ELECTRIC FIELD INDUCED BY AN EXTERNAL MAGNETIC FIELD - Lisewski, Tomasz; Mikołajczyk, Agnieszka; Abramik, Stanisław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The maximum induced electric field by external low frequency magnetic fields is considered when evaluating exposure of a body to magnetic field. The induced electric field cannot be measured but can only be assessed using analytical or numerical calculations. In the case of numerical simulations results are affected by errors caused by discretization of a body model being exposed. This error causes overestimation of the exposure level. The recommended ICNIRP approach to reduce errors is to average the results over a small cubic volume, and then take into account the 99th percentile value for a specific tissue. When evaluating exposure from small or local sources taking into account the 99th percentile value leads to underestimation. This paper propose a new method of reducing numerical errors using low pass filter. There is also presented results obtained directly from the simulation platform SEMCAD X compared to averaged values, and to results obtained using the new filtering method.